Aktivitas Antibakteri Nanopartikel Perak Hasil Green Synthesis Menggunakan Ektrak Kulit Buah Kemuning (Murraya Paniculata (L) Jack) - Doni Notriawan; Gustria Ernis; Risky Hadi Wibowo; Reza Pertiwi; Tessa Rianti Malau (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Antibacterial activity using silver nanoparticles synthesized using Murraya Paniculata (L) rinds extract has been carried out. This study aims to determine the antibacterial activity of green synthesized silver nanoparticles using Murraya Paniculata (L) rinds extract. Silver nanoparticles were synthesized by reacting AgNO3 with water extract of the Murraya Paniculata (L) rinds. Green synthesized silver nanoparticles were tested for antibacterial activity using Escherichia coli ATCC 8739. Silver nanoparticles synthesized using Murraya Paniculata (L) rinds extract were characterized using a UV-Vis spectrophotometer to confirm the formation of silver nanoparticles. The UV-Vis spectrophotometer results showed the formation of silver nanoparticles which was indicated by an absorption around 400-450 nm. The antibacterial activity test results of silver nanoparticles showed a strong inhibitory activity. Keywords: Green Synthesis, Silver Nanoparticles, Antibacterial, Echerichia Coli